The Human is Dead, Long Live the Algorithm!. Human-Algorithmic Ensembles and Liberal Subjectivity - Matzner, Tobias (Theory, Culture & Society)
The article analyzes the relation of humans and technology concerning so called ‘intelligent’ or ‘autonomous’ algorithms that are applied in everyday contexts but are far removed from any form of substantial artificial intelligence. In particular, the use of algorithms in surveillance and in architecture is discussed. These examples are structured by a particular combination of continuity and difference between humans and technology. The article provides a detailed analysis of boundary practices that establish continuity and oppositions between humans and information technology, referring to their exemplary depiction in movies. Both strands of boundary practices have the potential to challenge as well as sustain the position of the human as liberal, autonomous subject. Finally, it is shown how the particular combination of continuity and difference that structures the use of algorithms maintains the power of liberal, autonomous subject positions, while the shift of decisions to the algorithms seems to decenter the human.